Fort Moraya as an Educational Medium: Revitalizing History in Twenty-First-Century Learning - Nedia Lestari Sihombing; Miftahuddin (Indonesian Journal of Advanced Research, 2026)
Fort Moraya represents an important historical trace of the Minahasa people’s struggle to defend their territory. The site is located in Tondano, Minahasa Regency, North Sulawesi Province, Indonesia. In the context of twenty-first-century history education, the increasing accessibility of historical information across regions has broadened intellectual horizons and reshaped the way historical heritage is understood and utilized as a learning resource. The Fort Moraya site, which was once nearly forgotten, needs to be revitalized and reintroduced as part of the collective historical memory. In the twenty-first century, Fort Moraya functions as a multifaceted educational medium that supports various forms of learning and research. It serves as an educational resource for archaeologists, historians, architecture researchers, prospective tour guides, students, and the general public, attracting not only local and national communities but also international audiences. The site provides opportunities for site-based learning, historical inquiry, and heritage education through direct engagement with material remains and cultural narratives of the Minahasa people. To sustain its educational relevance, the Minahasa Department of Culture and Tourism has continuously undertaken revitalization and renovation efforts to preserve the site and enhance its role in supporting intellectual and cultural development. This study employs historical and qualitative research methods, utilizing documentary data obtained from the Minahasa Department of Culture and Tourism, complemented by field observations at the Fort Moraya site. The findings highlight the significance of Fort Moraya as a local historical heritage site with strong potential as an educational medium in twenty-first-century history learning.